SETD2, GIGYF2, FGFR3, BCR, KMT2C, and TSC2 as candidate genes for differentiating multilocular cystic renal neoplasm of low malignant potential from clear cell renal cell carcinoma with cystic change - Sung Han Kim; Weon Seo Park; Jinsoo Chung (Investigative and Clinical Urology, 2019)
Purpose: Multilocular cystic renal neoplasm of low malignant potential (MCRNLMP) and clear cell renal cell carcinoma with cystic change (MCRCC) have different prognoses despite similar histologic characteristics. The aim of this study was to identify differentially mutated genes in resected tumor specimens from patients diagnosed with MCRNLMP and MCRCC using a kidney cancer gene panel. Materials and Methods: Between 2009 and 2016, 13 MCRNLMP and 17 MCRCC cases were selected. Tumor tissues from 5 MCRNLMP and 16 MCRCC cases were subjected to gene sequencing to detect mutations among 88 genes selected from a kidney cancer gene panel after quality control. Fisher's exact test was used to compare gene mutation profiles between the two diseases. Genes were considered to be positive for mutation according to the presence of an in-frame/frameshift deletion or insertion, missense/nonsense mutation, or multi-hit mutation. Results: During a median follow-up period of 66.2 months, there was only one case of MCRCC recurrence among all 30 patients. Target gene sequencing showed that 35 genes tended to be more frequently positive in either disease group, with six genes showing a significantly different frequency of mutation between the groups: GIGYF2 (odds ratio [OR], 5.735), FGFR3 (OR, 6.787), SETD2 (OR, 4.588), BCR (OR, 6.266), KMT2C (OR, 8.167), and TSC2 (OR, 4.474). Conclusions: Six candidate genes showed significantly different mutation patterns between MCRNLMP and MCRCC, providing insight into their pathogenic mechanisms and differential prognoses.